Ergative Constructions in Yorùbá: A Minimalist Approach - Jelili Adewale Adeoye; Owoyele Oluwasegun Joseph (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2023)
Existing studies on Yorùbá syntax have shown that there are controversies among scholars on the motivation for DP movement in ergative construction in the language. Scholars have suggested theta theory and pragmatics as the explanation, while others lay credence to case or extended project principle. None of the existing works have address DP movement in ergative construction in Yorùbá with insight of the Minimalist Program. This present research dwells on Chomsky (1995, 1998 2000 &2001) Minimalist Program with Yorùbá internal language evidence to explain DP movement in the ergative construction. Findings in study show that the only DP in ergative construction performs dual functions. It is the subject based on the syntactic position and morphological marking, while it also functions as object because it bears theme theta role.